Cost-effectiveness of dabigatran etexilate for the prevention of stroke and systemic embolism in atrial fibrillation: A Canadian payer perspective - Sorensen, Sonja V.; Kansal, Anuraag R.; Connolly, Stuart; Peng, Siyang; Linnehan, John; Bradley-Kennedy, Carole; Plumb, Jonathan M. (Thrombosis and Haemostasis, 2011)
Oral dabigatran etexilate is indicated for the prevention of stroke and systemic embolism in patients with atrial fibrillation (AF) in whom anticoagulation is appropriate. Based on the RE-LY study we investigated the cost-effectiveness of Health Canada approved dabigatran etexilate dosing (150 mg bid for patients <80 years, 110 mg bid for patients ≥80 years) versus warfarin and “real-world” prescribing (i.e. warfarin, aspirin, or no treatment in a cohort of warfarin-eligible patients) from a Canadian payer perspective. A Markov model simulated AF patients at moderate to high risk of stroke while tracking clinical events [primary and recurrent ischaemic strokes, systemic embolism, transient ischaemic attack, haemorrhage (intracranial, extracranial, and minor), acute myocardial infarction and death] and resulting functional disability. Acute event costs and resulting long-term follow-up costs incurred by disabled stroke survivors were based on a Canadian prospective study, published literature, and national statistics. Clinical events, summarized as events per 100 patient-years, quality-adjusted life years (QALYs), total costs, and incremental cost effectiveness ratios (ICER) were calculated. Over a lifetime, dabigatran etexilate treated patients experienced fewer intracranial haemorrhages (0.49 dabigatran etexilate vs. 1.13 warfarin vs. 1.05 “real-world” prescribing) and fewer ischaemic strokes (4.40 dabigatran etexilate vs. 4.66 warfarin vs. 5.16 “real-world” prescribing) per 100 patient-years. The ICER of dabigatran etexilate was $10,440/QALY versus warfarin and $3,962/QALY versus “real-world” prescribing. This study demonstrates that dabigatran etexilate is a highly cost-effective alternative to current care for the prevention of stroke and systemic embolism among Canadian AF patients.
Keywords: Anticoagulation; dabigatran etexilate; warfarin; stroke; cost-effectiveness; atrial fibrillation